System of exercises to potentiate coordination in first category basketball athletes in Guantanamo - Liuver Burke-Marsan; Alexi Bartelemí-Sayú (Universidad de Guantánamo, 2019)
A diagnosis was made to analyze the coordination in first category basketball players in the province of Guantánamo. The methods used were from the theoretical level analysis-synthesis, inductive-deductive and systemic-structural- functional. From the empirical level, observation, document analysis and experiment were used. How the interview and survey techniques. From the mathematical level, the arithmetic mean and the percentage calculation. The proposal is based on the guidelines issued by the comprehensive training program for the preparation of the athlete. The exercise system was evaluated as relevant, corroborating the consultations carried out with coaches, advisors and methodologists, constituting a tool to improve this capacity.